ORIENTATIONS OF THE POLICY OF PRESERVING THE HUMAN CAPITAL OF UKRAINE IN THE CONDITIONS OF WAR - HRYHORUK, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article focuses on the issues of preservation and development of Ukraine’s human capital in the conditions of a full-scale war. Emphasis is placed on the existential challenges of the level of national security and stability of Ukraine, such as the rapid and large-scale external migration of Ukrainians, large-scale volumes of internally displaced persons and the actualization of the problems of overcoming the social vulnerability of the population, the destruction of homes and social and housing-communal infrastructure on a large area of the country’s territory, the deterioration of the quality of life and significant difficulties and social issues at the stage of post-war reconstruction of our state. That is why the aim of the study was to generalize the sources and consequences of the loss, as well as to determine the guidelines of the state policy of preserving the human capital of Ukraine in the conditions of a full-scale war. It was concluded that the main directions of formation and implementation of the state policy of preserving human capital of Ukraine are: (1) regulation of migration processes and inhibition of migration losses; (2) conducting a proactive policy of overcoming the social vulnerability of the population; (3) elimination of disparities and balancing of the leading characteristics of the functioning of regional labor markets; (4) creation of prerequisites for the growth of business activity of the population, development of entrepreneurship and self-realization; (5) increasing human capital by means of proactive youth policy, especially in the fields of education, science, culture and art. The scientific novelty of the research results lies in the development of a methodical approach to the identification of challenges and threats to the preservation and loss of the country’s human potential in war conditions. The practical significance of the research results lies in the development of a system of measures, the implementation of which will allow preserving and increasing the human potential of Ukraine in an environment of aggressive war.